EFFECT OF CBN POLICY TO CHANGE OF NAIRA NOTE ON PADDY RICE PRICING IN GUMA LOCAL GOVERNMENT AREA, BENUE STATE, NIGERIA - Iorlamen, T.R.; Tsue, P.T.; Ivom, A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This study was carried out to analyze the effect of CBN policy (change of naira note) December 15, 2022 on paddy rice pricing in Guma Local Government Area, Benue state. Specific Objective was to access perception of policy implementation by the respondents, access pricing of rice during this period, access quatity of rice sales and access gross margin before and during the period of policy. Multistage sampling and simple random sampling techniques was used to select 100 paddy rice marketers in the study area. Descriptive statistic and Gross margin were used to analyze the data for this study. The result showed that almost all (99%) of the respondents were aware of policy and agreed that the policy implementation was not favourable as it mostly (98%) affected buying and selling of the paddy rice. Majority (98%) of the respondents experienced reduced pricing of paddy rice as the mean price of paddy rice fell from N34,650 to N22,300 during the period of policy implementation. The result further showed that the mean quantity of paddy rice sold reduced from 62 bags per month to 23bags per month during the period of policy. The results also showed that most (94%) of the respondents had their mean monthly gross margin reduced from N193,550 to N59920. The null hypothesis was rejected, as there was a significant difference in the mean gross margin before the CBN policy and during CBN policy at t value (< 8.75< 0.00) which was significant at 1% probability. The study concludes that, the implementation of Naira change policy was not favorable as it affected buying and selling of the paddy rice, it therefore recommends that policies on change of Naira or currency should be criticaly studied by experts before initiating and /or implementing such policies, to avoid untold hardship for the citizens.